New locality record of the Lofty bath white butterfly Pontia callidice (Hübner, 1800) in Nepal - Suwal, Sanej Prasad; Hengaju, Krishna Dev; Kusi, Naresh (Nepalese Journal of Zoology, 2021)
Lofty bath white Pontia callidice is a little-known butterfly of Nepal, reported only from Darchula district, Far Western Nepal. We recorded the new distribution eastward of this species 166 km N-E far from its previous range in Talung and Gyaukhola Valley of Upper Humla in July 2017 at elevations between 4400 to 4829 m above sea level. This is also the highest elevation record of this species.